“BURNOUT” AND “HAVOTIR” AS DISCURSIVE CONCEPTS: A THEORETICAL DISCUSSION OF PRAGMATIC ORIENTATIONS (SCIENCE TIME JOURNAL, 2026)
This article offers a theoretical discussion of how the concept burnout in English and havotir in Uzbek are constructed in contemporary motivational discourse. Drawing on pragmatic theory and lexical typology, the article identifies the distinct pragmatic orientations of the two concepts. English burnout is constructed through operational-tactical discourse oriented toward scheduling, reframing,and identity-renarration. Uzbek havotir is constructed through contemplative-restorative discourse oriented toward recognition, reflection, and restorative pause. The article discusses theoretical and translation-theoretic implications of these pragmatic divergences and contributes to the comparative pragmatics of contemporary mental-state discourse.